Gestational trophoblastic neoplasia treatment at the Butaro Cancer Center of Excellence in Rwanda - Nzayisenga, I; Segal, R; Pritchett, N; Xu, MJ; Park, PH; Mpanumusingo, EV; Umuhizi, DG; Goldstein, DP; Berkowitz, RS; Hategekimana, V; Muhayimana, C; Rubagumya, F; et al. (American Society of Clinical Oncology, 2016)
Purpose Gestational trophoblastic neoplasia (GTN) is a highly treatable disease, most often affecting young women of childbearing age. This study reviewed patients managed for GTN at the Butaro Cancer Center of Excellence (BCCOE) in Rwanda to determine initial program outcomes.